2022
DOI: 10.1186/s13052-022-01387-3
|View full text |Cite
|
Sign up to set email alerts
|

Early neurodevelopmental outcomes in children with asymptomatic congenital CMV infection

Abstract: Background Approximately 85–90% of congenital cytomegalovirus infections (cCMV) are asymptomatic. Few studies have investigated early and long-term neurodevelopmental outcomes in children with asymptomatic cCMV (acCMV), and the data is contradictory. In the present study, we did investigate the effect of cCMV asymptomatic infection on neurological outcomes and in cognitive, language and motor development at 6 months of age. Methods Fifty-six childr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 39 publications
1
20
0
Order By: Relevance
“…The definition of symptomatic infection remains under debate. There are no definite diagnostic criteria to precisely identify the two conditions [34,35]. Consensus recommendations defining asymptomatic cCMV infection with isolated SNHL (with no apparent abnormalities to suggest cCMV disease, but sensorineural hearing loss (≥21 decibels) have been pub-lished [36].…”
Section: Discussionmentioning
confidence: 99%
“…The definition of symptomatic infection remains under debate. There are no definite diagnostic criteria to precisely identify the two conditions [34,35]. Consensus recommendations defining asymptomatic cCMV infection with isolated SNHL (with no apparent abnormalities to suggest cCMV disease, but sensorineural hearing loss (≥21 decibels) have been pub-lished [36].…”
Section: Discussionmentioning
confidence: 99%
“…Neonates with asymptomatic cCMV are also at risk for abnormal neurodevelopment [6 ▪▪ ]. Studies have reported that 14, 11, and 19% of infants with asymptomatic cCMV had developmental concerns on Bayley-III at 6, 12, and 24 months of age, respectively [51 ▪ ,55 ▪ ]. Meta-analysis showed that 14% of asymptomatic newborns following maternal primary CMV infection had neurodevelopmental disorders in childhood [52].…”
Section: Neurological and Developmental Outcomes Of Congenital Infect...mentioning
confidence: 99%
“…Human cytomegalovirus (HCMV) is a common pathogen with a worldwide infection rate ranging from 60 to 90% of the population (1-3). Though infected individuals are typically asymptomatic, a subset of congenital infections (10-15%) demonstrate a risk to fetal health and development (4)(5)(6)(7)(8)(9). In such cases, a wide range of neurological symptoms may occur, including hearing impairment, cognitive deficits, learning/language disorders, and microcephaly (2,(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, several studies have also examined neurological effects present in individuals with asymptomatic congenital infections (2,4,12,13). Together, these studies highlight HCMV's ability to negatively impact development and activity within the central nervous system (CNS).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation